UPACARA MANUSA YADNYA DALAM LONTAR SMARAREKA - I Gst. Ngr Wiriawan (Kalangwan Jurnal Pendidikan Agama, Bahasa dan Sastra, 2020)
Upacara manusa yadnya (ceremony related to human life) is represented as one of way to maintain the universe balance. Since the ceremonies aim to honor humans as the main life cycle support. Many literary work inherited to Balinese people that become the guidelines in implementing these ceremonies, one of them is smarareka manuscript. Smarareka describes the history of universe creation, ehich contains how to maintain the balance of universe (buana agung) and humans (buana alit). Related to honor the humans, the manuscripts explained human brings the result of deeds from their previous life or called karma. These are in the form of illness, disaster, etc, that can become a barrier for their human life. Furthermore, it needs some ceremonies to re-cleanse human since they were born. Some ceremonies mention at the manuscript are placenta burial, ceremony when babies umbilical cord was broken, and balinese birthday ceremony.